(untitled) (Bioagro, 2023)
Various bacterial diseases affect rice (Oryza sativa L.), causing foliar lesions and grain discoloration, symptoms observed in rice-growing areas of Venezuela. The objective of this study was the characterization, inoculation and evaluation of the main symptoms produced by bacterial strains in rice, belonging to the Danac Foundation’s collection of pathogens. The strains were reactivated and presumptive, physiological and biochemical tests carried out, based on a descriptive evaluation of the symptoms. The conventional characterization allowed to corroborate the presence of Xanthomonas oryzae pv. oryzae (Xoo), Acidovorax avenae, Pantoea agglomerans and Burkholderia glumae, which were positive (100%) in the pathogenicity tests. Since P. agglomerans is the most frequent and ubiquitous species in the rice-growing areas of Venezuela, three different inoculation methods were tested on it, as well as the effect of the different strains on the size of the lesion in leaves. In addition, the percentage of grains stained by the effect of inoculation with the different bacterial species was measured in the panicle. A completely randomized design with three replicates was used. The largest size of the lesion on the leaves was detected by the scissor and spray methods, being the variety ’Colombia 21’ the most affected. In the evaluation of the panicle, the strains of B. glumae and Xoo showed a higher percentage of stained grains, without significant differences between them, while the variety of rice ’IR8’ was the most susceptible, regardless of the strains inoculated.